Drug Repurposing - Hypothesis, Molecular Aspects and Therapeutic Applications 2020
DOI: 10.5772/intechopen.93344
|View full text |Cite
|
Sign up to set email alerts
|

Drug Repurposing in Dermatology: Molecular Biology and Omics Approach

Abstract: The withdrawal of several blockbuster drugs due to severe adverse effects and the failure of several developed drugs in clinical trials raised questions about the efficacy of current approaches of drug discovery. Moreover, the limitation of resources and the long and costive process of drug discovery made a lot of pharmaceutical companies to employ drug repurposing strategies to get new insights about activities that were not considered during their initial discovery. The development of therapeutics for treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For example, glycoalkaloids from potato tubers can inhibit the germination of weed seeds and suppress the growth of soil-borne pathogens [3]. Glycoalkaloids can also modulate the expression of genes involved in plant stress responses and biosynthesis of other secondary metabolites [1]. Studies have shown that glycoalkaloids are involved in the regulation of plant growth and development, including the formation of roots, shoots, and leaves.…”
Section: Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glycoalkaloids from potato tubers can inhibit the germination of weed seeds and suppress the growth of soil-borne pathogens [3]. Glycoalkaloids can also modulate the expression of genes involved in plant stress responses and biosynthesis of other secondary metabolites [1]. Studies have shown that glycoalkaloids are involved in the regulation of plant growth and development, including the formation of roots, shoots, and leaves.…”
Section: Biological Activitymentioning
confidence: 99%
“…Drug repositioning or repurposing is an interesting way to reuse old drugs for new indications; For example, chloroquine, an old antimalarial drug, showed promising results for treating COVID-19, interfering with multidrug resistance (MDR) in several types of cancer, and chemo-sensitizing human leukemic cells. There is a great economic impact of drug repurposing on drug discovery for the treatment of many skin infectious diseases, neurological disorders, cancers, and orphan diseases [1]. In this aspect, the liver research laboratory (FAB-Lab, Faculty of Pharmacy, Mansoura University, Mansoura, and Egypt) has utilized several approaches for not only optimizing and enhancing the therapeutic effect of the commonly available natural products but also recognizing novel applications for them so that one therapeutic agent could be used for the treatment of several or complex conditions adopting different strategies for drug repositioning [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introduction 11 Drug Repositioningmentioning
confidence: 99%
“…In that aspect, the liver research laboratory (FAB-Lab, Faculty of Pharmacy, Mansoura University, Mansoura, Egypt) has applied several approaches for not only improving the pharmacological effect of easily accessible natural products, but also identifying new applications for them. Drug repositioning or repurposing may reveal a new approach to rediscover new uses for clinically approved existing old drugs [32]. This book revealed the theory, applications, and/or hazardous outcomes on drug discovery in different disciplines in medicine; e.g.…”
Section: Drug Repurposing and Covid-19mentioning
confidence: 99%
“…This book revealed the theory, applications, and/or hazardous outcomes on drug discovery in different disciplines in medicine; e.g. dermatology [33,34], cancer [35][36][37], and neurological disorders [38].…”
Section: Drug Repurposing and Covid-19mentioning
confidence: 99%
“…Despite the considerable concern and investment in the production of new medicine, some could not be adequately used for existing indications owing to the lack of effects or side effects arising in the preclinical or clinical stages. Drug repositioning is now emerging as a new approach to rediscovering new indications of drugs already approved, rather than starting at the beginning stage of drug production [4].…”
Section: Introductionmentioning
confidence: 99%